The school librarians of Soroca in the Mass-Media (Confluenţe Bibliologice, 2026)
The work represents a bibliographical synthesis that brings together articles and materials published by school librarians from Soroca district in various local and national periodicals. The bibliography highlights the active presence of specialists in the mass media by addressing fundamental themes for the education and culture system.